2022
DOI: 10.3390/molecules27155038
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyquingdainone Induces Apoptosis in Leukaemia and Lymphoma Cells via the Mitochondrial Pathway in a Bcl-2- and Caspase-3-Dependent Manner and Overcomes Resistance to Cytostatic Drugs In Vitro

Abstract: Isatis tinctoria and its indigo dyes have already provided highly active anti-leukaemic lead compounds, with the focus mainly being on indirubin, whereas indigo itself is inactive. There are many more indigoids to find in this plant extract, for example, quingdainone, an indigoid derived from tryptanthrin. We present here a new synthesis of hitherto neglected substituted quingdainones, which is very necessary due to their poor solubility behaviour, and a structure-dependent anti-leukaemic activity study of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Dihydroxyquingdainone, a tryptanthrin analog, inhibits growth of lymphoma cells through the modulation of intrinsic apoptosis and caspase-3 activation. 38 Our data demonstrated that CIQ dose-dependently induced apoptosis in breast cancer cells. Furthermore, for caspase-3-expressing MDA-MB-231 cells, CIQ induce caspase-3 activation and the decreased of caspase-8 were observed.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Dihydroxyquingdainone, a tryptanthrin analog, inhibits growth of lymphoma cells through the modulation of intrinsic apoptosis and caspase-3 activation. 38 Our data demonstrated that CIQ dose-dependently induced apoptosis in breast cancer cells. Furthermore, for caspase-3-expressing MDA-MB-231 cells, CIQ induce caspase-3 activation and the decreased of caspase-8 were observed.…”
Section: Discussionmentioning
confidence: 50%
“…Pathania et al 22 reported that a synthetic tryptanthrin derivative causes apoptosis through inducing caspase activation and suppressing STAT3 signaling in leukemia cells. Dihydroxyquingdainone, a tryptanthrin analog, inhibits growth of lymphoma cells through the modulation of intrinsic apoptosis and caspase‐3 activation 38 . Our data demonstrated that CIQ dose‐dependently induced apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, we tested the complex on cytarabine-resistant MaKo cells (co-resistances: fludarabine, cladribine, clofarabine, cyclophosphamide, and vincristine) [ 9 ], methotrexate-resistant JeBa cells (co-resistances: mitoxantrone, idarubicin, daunorubicin, doxorubicin, and epirubicin) [ 42 ], and etoposide-resistant JeFri cells (co-resistances: cytarabine and methotrexate) [ 9 ], each in comparison to the baseline Nalm-6 cell line. In all experiments, HB324 was able to overcome the resistant cells, similarly to that shown for the NaKu cells (see Supplementary Materials, Figures S5–S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, indirubin and its derivatives are currently being discussed to overcome imatinib resistance in CML [75]. Other published data have shown that an indigoid derivative can overcome chemoresistance in leukaemia cells [76] and that I3M sensitises multiple myeloma cells to bortezomib-induced apoptosis and overcomes bortezomib resistance via proteasome inhibition [77].…”
Section: Discussionmentioning
confidence: 99%